DEVELOPMENT OF WALLAGRI TOURISM DESTINATION BASED ON COMMUNITY EMPOWERMENT THROUGH ENGLISH LANGUAGE TRAINING AND TOURISM PACKAGING - Kemala, Zia; Astiana, Rachmat (LPPM Univ. Ibn Khaldun Bogor, 2025)
This Community Service Program aims to develop Kampung Wallagri as a tourism destination based on community empowerment through English language training and tourism packaging. Kampung Wallagri has rich cultural and natural tourism potential but has not been optimized in attracting international tourists due to the community's limited ability to communicate in English and package tourism products effectively. The program is implemented using a participatory method, including planning, implementation, evaluation, and mentoring stages. The training covers basic English communication for tourism, guiding techniques, and tourism packaging, conducted through lectures, discussions, drills, and role-playing. The program results show an improvement in the community's English communication skills and tourism product presentation, which is expected to enhance the tourist experience and local income. The program's outputs include increased community competence, scientific article publications, and a sustainable development plan supported by various stakeholders within the pentahelix framework. This program strengthens collaboration between academia, government, and the community to build sustainable and inclusive tourism.